FC 111: A Comorbidity Index and Pretransplant Physical Status Predict Survival in Older Kidney Transplant Recipients. (3rd May 2022) - Tsarpali, Vasiliki; Midtvedt, Karsten; Lønning, Kjersti; Bernklev, Tomm; Åsberg, Anders; Von der Lippe, Nanna; Varberg Reisater, Anna; Heldal, Kristian
Abstract: BACKGROUND AND AIMS: Regardless of age, kidney transplantation (KT) is considered the optimal treatment for patients with end-stage kidney disease (ESKD). In the increasing elderly ESKD population, KT should be reserved for carefully selected candidates who are expected to experience favorable outcomes. We aimed to prospectively evaluate pre-transplant recipient factors that may predict post-transplant patient survival and can eventually guide therapeutic decisions in elderly with ESKD. METHOD: Recipient factors were evaluated in KT candidates aged ≥65 years, who were enlisted for KT between January 2013 and November 2016 at the Norwegian national transplant centre. Pretransplant comorbidity was assessed at waitlisting, according to the Liu Comorbidity Index (LCI). Self-reported health-related quality of life was assessed using the Kidney Disease Quality of Life Short Form version 1.3 (KDQOL-SF). The Cox proportional hazard regression was used to evaluate predictors of patient survival. RESULTS: We included 289 waitlisted candidates, of whom 192 received a deceased brain-dead donor kidney. Mean age at KT was 72 (4.1) years, 133 (69%) were male, 47 (24%) were transplanted preemptively and 80% received an expanded criteria donor organ. During a median observation time of 4.6 (3.2–6.3) years post-KT, 66 recipients died. LCI ≤ 3 was observed in 136 recipients (71%), between 4–6 in 39 recipients (20%) and 17 recipients (9%) had LCI ≥ 7. Elevated LCI ≥ 4 predicted poor patient survival, and was associated with a 2.2-times increase in mortality risk (Figure 1 ). In recipients with LCI ≥ 4, dialysis ≥2 years comprised a 2.5-fold higher mortality risk, compared with recipients on dialysis ≤2 years (Figure 2 ). Self-reported pretransplant physical function was also proven to be a significant positive predictor of survival, with scores ≤60 being associated with a 2-fold increase in mortality risk. CONCLUSION: The implementation of LCI and a physical function score during the evaluation of older kidney transplant candidates may improve the selection and thereby optimize post-transplant outcomes.